2019
DOI: 10.1002/jcsm.12477
|View full text |Cite
|
Sign up to set email alerts
|

The Copenhagen Sarcopenia Study: lean mass, strength, power, and physical function in a Danish cohort aged 20–93 years

Abstract: BackgroundDespite no international consensus on the diagnostic criteria for sarcopenia, low lean mass, muscle strength, and physical function are important risk factors for disability, frailty, and mortality in older individuals, as well as in a wide range of patients with muscle loss. Here, we provide a population‐based reference material of total and regional lean body mass, muscle strength/power parameters, and physical function in a healthy cohort of Danish men and women across the lifespan.MethodsVoluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
144
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(164 citation statements)
references
References 48 publications
14
144
3
3
Order By: Relevance
“…The rate of MF fatigue would not be affected in a major way even if an awaited decline in mechanic output from muscle strength and power measurements (due to axonal and glycolytic muscle fiber loss) was well compensated (McKinnon et al 2015). It is worth noting that early declines in muscle power function seem more greatly associated with limitations in activities and mobility than muscle strength (Reid and Fielding 2012;Suetta et al 2019). Thus, the very early detection of individuals with or without cLBP who are in their 50s or 60s and who would be classified to be at an increased risk for sarcopenia (in their later age) could allow initiation of early interventions in these individuals; this would reduce the health burden of sarcopenia (Calvani et al 2017;Ciolac and Rodrigues-da-Silva 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of MF fatigue would not be affected in a major way even if an awaited decline in mechanic output from muscle strength and power measurements (due to axonal and glycolytic muscle fiber loss) was well compensated (McKinnon et al 2015). It is worth noting that early declines in muscle power function seem more greatly associated with limitations in activities and mobility than muscle strength (Reid and Fielding 2012;Suetta et al 2019). Thus, the very early detection of individuals with or without cLBP who are in their 50s or 60s and who would be classified to be at an increased risk for sarcopenia (in their later age) could allow initiation of early interventions in these individuals; this would reduce the health burden of sarcopenia (Calvani et al 2017;Ciolac and Rodrigues-da-Silva 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 628 older subjects (346 women and 282 men) participated in this investigation (Table 3). The sample was composed of older people (≥ 60 years old) participating in the Copenhagen Sarcopenia Study 46 , a population-based cross-sectional study that included men and women aged 20-93 years living in the Copenhagen metropolitan area (Denmark). Exclusion criteria included acute medical illness, surgery within the last three months, ongoing medication known to affect body composition and/or reporting any history of compromised ambulation or prolonged immobilization.…”
Section: Participantsmentioning
confidence: 99%
“…Several studies have shown that regular resistance exercise effectively prevents sarcopenia in older adults, effects that may be further enhanced by simultaneously increasing protein intake [ 6 8 ]. However, clinicians rely on adequate disease-defining thresholds and guidelines to direct effective treatments, and implementation of the sarcopenia diagnose is currently hindered by a lack of international consensus over a common operational definition [ 9 ].…”
Section: Introductionmentioning
confidence: 99%